Advancements in Pathological Analysis: Techniques and Innovations in Diagnostic Medicine - Dhanoun, Fahd Tomaa Thamer; Neama, Safa Hassan Ali; ali, Sara ahmed hassan; Jabr, Zahraa Faris Hadi (American Journal of Biology and Natural Sciences, 2025)
An overview of new possibilities and challenges in digital image analysis of pathology is given. This technology is in the intersection of computer science, optics, and biomedicine, with clear economic consequences concerning both the research process and possible routine applications. A short practical guide is proposed for those dealing with digital images in pathology for research or in clinical practice for better standardization of the task. This paper indicates that digital image analysis is an obligation and everyone has the mission to be well informed about the opportunities and methodological constraints for the benefit of patients as well as the whole environment. Histochemistry and Cytochemistry published the first issue in 1953, it was the birth year of both the magazine and of the digital computer. Over previous decades, the opinions that deduced operational research to a passing fashion and questioned why electron microscopy was ever invented come to mind. All technologies are fashionable, i.e., rapidly developing and then disappearing, as are the neighboring continents by geographical separation. Digital imaging and digital image analysis seemed to belong to this class. However, as noted herein, a need for arriving at diagnoses “more precisely and firmly grounded in basic scientific knowledge” is increasingly proclaimed. This unsettled situation accounts for the technological survival of light and electron microscopy and results in their closest alliance with computer-based analysis. How long will it last? The future of imaging and automated applications, therefore, remains controversial. The purpose of the present article is to give a cross-disciplinary update on major opportunities and methodological constraints in the field of digital (or computer-aided) image analysis, as well as research strategies and applications therewith associated. This paper may seem rather lengthy; however, the non-expert is urged to consult key references in the text and at the end for a more succinct introduction and guidelines.